Clinical and neurophysiological features of mental disorders in patients with HIV infection - N. G. Neznanov; N. B. Khalezova; M. A. Hobeysh; N. G. Zakharova; M. Ya. Kissin (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2019)
Summary. Te aim of the study was to study the clinical signifcance of changes in bioelectric activity for the purpose of identifying them as biological markers of mental disorders in patients with HIV infection. A cross-sectional study was conducted to diagnose mental disorders and search for neurophysiological markers in 62 patients with HIV infection at the St. Petersburg Center for the Prevention and Control of HIV and Infectious Diseases.Results: 50% of patients with HIV infection without abuse disorders have mental disorders characterized mainly by adaptive reactions and mild cognitive impairment. Normal indicators of bioelectrical activity were determined in 16.1% of 62 patients. In the majority of patients (59.7%), bioelectrical activity was determined with a predominance of excitation in the medio-diﬀerent areas and a decrease in activity of the cerebral cortex. In 41.9% of patients, the processes of CNS excitation were increased in the form of an intensifcation of the reaction to photostimulation. Neurophysiological diﬀerences were revealed in patients with neurotic and stress-related disorders and organic changes in the CNS. For neurotic disorders in comparison with organic disorders, the EEG was normal or the disorganized type with predominance of alpha and beta activity were more likely, while in the case of organic disorders the desynchronous type of EEG was more ofen noted. Te development of psycho-organic syndrome in HIV patients is confrmed by deep restructuring of bioelectrical activity in the anterior parts of the brain.